Microstructure, Tensile Property, and Surface Quality of Glass Fiber-Reinforced Polypropylene Parts Molded by Rapid Heat Cycle Molding. (26th March 2020) - Liu, Feng; Li, Taidong; Xu, Fuyu; Li, Jiquan; Jiang, Shaofei
Abstract : The microstructure of a molded product considerably influences its macroscopic properties. In this study, the influence of molding process on microstructure, tensile property, and surface quality was explored on the glass fiber-reinforced polypropylene (GFRPP) parts molded by rapid heat cycle molding (RHCM) and conversion injection molding (CIM). Tensile strength and surface gloss were chosen to measure macroscopic properties of the molded parts. The microstructure including multilayer, fiber orientation, crystallinity, and fiber-matrix bonding strength were analyzed by simulations, scanning electron microscopy, wide-angle X-ray diffraction, and dynamic mechanical analysis. The relationship between the macroscopic properties and microstructure of the RHCM samples was also discussed. The results indicate that as the mold cavity surface temperature increases, the tensile strength increases firstly and decreases thereafter. The tensile strength of RHCM parts reached the maximum at the mold heating temperature of 60°C. It is also observed that the surface gloss of the sample increases as the mold cavity surface temperature rises, and the increase of surface gloss decreases distinctly with the mold heating temperature higher than 90°C.